2019
DOI: 10.4103/aja.aja_47_19
|View full text |Cite
|
Sign up to set email alerts
|

Role of tumor-associated immune cells in prostate cancer: angel or devil?

Abstract: Prostate cancer is the most common malignancy in the reproductive system of older males. Androgen deprivation therapy (ADT) is an important treatment for prostate cancer patients. However, almost all prostate cancer patients unavoidably progress to the castration-resistant stage after ADT treatment. Recent studies have shown that tumor-associated immune cells play major roles in the initiation, progression, and metastasis of prostate cancer. Various phenotypes of tumor-associated immune cells have tumor-promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 53 publications
0
14
0
1
Order By: Relevance
“…We previously reported that down-regulation of SFMBT2 promotes prostate cancer metastasis through the up-regulation of MMPs and that expression level of SFMBT2 inversely correlates with the prognosis of prostate cancer patients such as invasion and metastasis [ 26 ]. Given that infiltration of adipocytes or macrophages into the tumor microenvironment contributes to prostate cancer progression [ 27 , 28 ], we further investigated whether SFMBT2 regulates the expression of chemokines, which are linked to cell infiltration. Because poorly metastatic LNCaP cells express a relatively high level of SFMBT2 compared with highly metastatic PC3 and DU145 cells and because LNCaP cells expressing a low expression level of SFMBT2 by RNA interference showed enhanced migration and invasion [ 26 ], we used mainly LNCaP cells as a cell model in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that down-regulation of SFMBT2 promotes prostate cancer metastasis through the up-regulation of MMPs and that expression level of SFMBT2 inversely correlates with the prognosis of prostate cancer patients such as invasion and metastasis [ 26 ]. Given that infiltration of adipocytes or macrophages into the tumor microenvironment contributes to prostate cancer progression [ 27 , 28 ], we further investigated whether SFMBT2 regulates the expression of chemokines, which are linked to cell infiltration. Because poorly metastatic LNCaP cells express a relatively high level of SFMBT2 compared with highly metastatic PC3 and DU145 cells and because LNCaP cells expressing a low expression level of SFMBT2 by RNA interference showed enhanced migration and invasion [ 26 ], we used mainly LNCaP cells as a cell model in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Given that reciprocal interaction between infiltrated cells and prostate cancer cells plays a critical role in metastasis [ 27 , 28 ], we further investigated the effects of infiltrated preadipocytes and TAMs on migration and invasion of prostate cancer cells. LNCaP cells stably transfected with control or SFMBT2 shRNA were incubated with culture medium from 3T3-L1 preadipocytes or TAMs.…”
Section: Resultsmentioning
confidence: 99%
“…T regulatory cells (Tregs), tumor-associated macrophages (TAMs), tumor-infiltrating B lymphocytes (TILs), neutrophils, and myeloid-derived suppressor cells (MDSCs) are part of the infiltrated immune cell of the prostate tumor microenvironment. However, various studies have reported that the progression of PCa is influenced by the tumor-associated immune cells and inflammatory cytokines, such as IL-23 ( Ammirante et al, 2010 ; Si et al, 2013 ; Calcinotto et al, 2018 ; Wang et al, 2019 ; Zhang Z. et al, 2020 ). TAMs are a major component in the development of PCa, though the specific pathway for the release of cytokines, matrix metalloproteinases, and growth factors is still unknown ( Shimura et al, 2000 ; Arora et al, 2018 ).…”
Section: Castration-resistant Prostate Cancermentioning
confidence: 99%
“…HR Metastatic PCa Patients Have Decreased CD4 + T Cell Responsiveness to SARS-CoV-2 but not HCoV-229E Spike Glycoprotein-derived Peptides Compared with Healthy Male Volunteers As PCa can be associated with immunosuppression (Wu et al, 2019), we next examined whether HR metastatic PCa patients in our cohort had compromised responsiveness to SARS-CoV-2 and HCoV-229E peptide pools. We strati ed our cohort into groups of healthy male volunteers and HR metastatic PCa patients and compared the results from our enrichment experiments between these two groups and the peptide pools.…”
Section: Sars-cov-2 and Hcov-229e Spike Glycoprotein-derived Peptides Comparably Enriched The Cultured Cellsmentioning
confidence: 99%